Method for preparing smithsonite-cerusite by curing zinc and lead through carbonate and application of smithsonite-cerusite
By co-precipitation reaction of carbonate with zinc and lead cations, a series of solid solutions of rhodium-white lead ore are generated, which solves the pollution problem of heavy metals zinc and lead in the environment, and realizes its removal and long-term stacking in aqueous solution.
Patent Information
- Application Number
- CN202411754572.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
Improper emissions of heavy metals zinc and lead in mining, smelting, electroplating and other industries have led to environmental pollution and human health hazards. It is difficult for the existing technology to effectively remove these heavy metals and achieve long-term stacking.
The carbonate co-precipitation reaction with zinc and lead cations was performed to form a series of solid solutions of rhodium-white lead ore. The heavy metal was fixed in the solid solution by this method, and its stability was verified by drying and leaching tests.
The removal of heavy metal zinc and lead in aqueous solution is achieved, and the leaching concentration of heavy metals is significantly reduced in the aqueous environment under neutral and alkaline conditions, providing an effective method to treat lead-containing zinc waste slag and achieve long-term stacking.
Smart Images

Figure CN119591148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental safety and technology, and relates to a method and application of preparing smithsonite-cerussite by solidifying zinc and lead with carbonate. The method uses carbonate to solidify heavy metal zinc and lead at the same time to form a smithsonite-cerussite series solid solution. Background Art
[0002] Heavy metal pollution caused by wastewater, waste residue, dust, etc. generated during the beneficiation of lead and zinc mines affects the soil and groundwater in the mining area and surrounding areas. A large amount of heavy metals will be released and migrated under the action of surface biogeochemistry, thereby polluting the soil and rivers in the mining area and surrounding areas.
[0003] Lead is one of the common elements in nature. It is the raw material of cables, batteries and gasoline additives, and is also the main raw material of paints, coatings, pesticides and some medicines. At the same time, lead is also a widely distributed toxic metal. Its compounds can enter the natural environment through wastewater, waste gas and waste residue, causing serious environmental pollution and endangering human health. The sources of lead pollution include the "three wastes" of primary ore smelting, lead-acid batteries and electroplating wastewater, and the random stacking of lead-containing solid waste. Lead is a non-essential element for the human body. When the concentration of lead in the blood is greater than 1.2 μmol / L, it will cause lead poisoning. Lead and its compounds cannot be absorbed and degraded in the human body. It is a highly cumulative poison that mainly accumulates in the blood, liver, and urinary system. It not only damages the human nervous system, but also damages the human immune system, reducing the body's ability to resist diseases. The symptoms of lead poisoning are mainly headache, dizziness, constipation, abdominal pain, soreness and swelling of the limbs, anemia, arteriosclerosis, peptic ulcers, toxic hepatitis and neurasthenia.
[0004] Zinc plays an important strategic role in the development of the national economy. Zinc and its alloys are mainly used in the fields of steel, metallurgy, machinery, electricity, chemical industry, light industry, military and medicine. They are essential metal elements for modern industry, agriculture, national defense and science and technology. At the same time, zinc is also a ubiquitous pollutant, which has attracted widespread attention from the perspective of environmental impact and human health hazards. These problems are mainly caused by the irregular discharge of aqueous solutions and waste residues from industries such as mining, smelting and electroplating, which allow heavy metal elements such as Zn (II) to enter the environment and cause environmental pollution. For example, due to intensive mining activities, heavy metal elements such as Zn (II) enter rivers. Although zinc is an essential trace element for mammals, it is toxic to fish and shellfish at the level allowed in drinking water. Zinc is one of the essential trace elements for the human body. It participates in the composition of more than 200 enzymes in the human body and is known as the "flower of life". The normal human body contains 2 to 2.5 grams of zinc, but excessive intake of zinc into the human body can cause poisoning. The zinc supply and the poisoning dose are very close, that is, the safety belt is very narrow. For example, the zinc supply of humans is 10-20 mg / day, while the poisoning dose is 80-400 mg. The symptoms of zinc poisoning include erosion of the mouth, pharynx and digestive tract, swelling of the lips and glottis, abdominal pain, diarrhea, vomiting, and water and electrolyte disorders; in severe cases, there may be crises such as increased blood pressure, shortness of breath, dilated pupils, shock, and convulsions.
[0005] As we all know, there are a lot of rocks on the surface of the earth, and large areas are covered by carbonate rocks. In terms of environmental pollution control, some naturally occurring minerals can use the adsorption properties of their mineral surfaces to remove heavy metals. These materials can provide a cheap substitute for wastewater containing heavy metals after modification. Existing studies have shown that heavy metals can be adsorbed on the surface of carbonates, which represents a potential important metal removal process in water and soil environments and waste systems. According to the distribution coefficient of anions and cations in the solid-liquid two phases, carbonate minerals can effectively isolate a variety of toxic cations in the solution, so precipitating carbonates from contaminated solutions may be an effective environmental remediation method. When divalent metal cations and carbonate anions exist in the aqueous solution at the same time, after a period of time, crystal nuclei with low energy barriers begin to form, and the supersaturated carbonate in the solution will precipitate in the form of crystals. Utilizing this mechanism, carbonates can be used to remove lead and zinc ions dissolved in the aqueous solution. The present invention provides a method for preparing smithsonite-cerussite by solidifying zinc and lead with carbonates, which is used to fix lead and zinc ions. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing smithsonite-cerussite by solidifying zinc and lead with carbonate. The prepared solid solution is subjected to X-ray diffraction (XRD), the leaching concentration of smithsonite-cerussite solid solution under the conditions of nitrogen degassed ultrapure water, air saturated ultrapure water, and carbon dioxide saturated ultrapure water is tested, and its stability is subjected to detailed experimental analysis, so as to provide a theoretical basis for exploring the migration and fate of lead and zinc in the environment.
[0007] A method for preparing a smithsonite-cerussite series solid solution by solidifying zinc and lead with carbonates, the specific steps of which are:
[0008] (1) Prepare fresh ultrapure water, weigh an appropriate amount of solid ammonium bicarbonate, and prepare a 0.5 mol / L ammonium bicarbonate solution for later use; weigh an appropriate amount of solid zinc nitrate, and prepare a 0.5 mol / L lead nitrate solution for later use; weigh an appropriate amount of solid lead nitrate, and prepare a 0.5 mol / L lead nitrate solution for later use.
[0009] (2) Use 0.5 mol / L Zn(NO3)2 and Pb(NO3)2 to prepare 25 mL of mixed solutions with different Pb / (Zn+Pb) molar ratios (see 'Specific Implementation Methods' for details) in a clean beaker.
[0010] (3) Take several clean 600 mL beakers and add the mixed solution according to the molar ratio in step (2).
[0011] (4) At room temperature, in a clean beaker, introduce industrial-grade carbon dioxide gas at a flow rate of 6-9 L / min into the mixed solution and set the stirring speed to 500 r / min.
[0012] (5) After aeration and stirring for 15 minutes, add 100 mL of NH4HCO3 solution to the mixed solution every 1 minute; a total of 500 mL of 0.5 mol / L NH4HCO3 solution was added.
[0013] (6) Seal the beaker with plastic wrap, measure the pH value of the supernatant after aging for 2 days, and filter it. During the filtration process, wash the beaker three times with ultrapure water and once with anhydrous ethanol.
[0014] The carbonate solidified zinc and lead obtained in the present invention is used to prepare a series of solid solutions of smithsonite-cerussite, which is applied to the removal of lead and zinc in wastewater and the long-term stacking of lead-zinc waste residue in the environment. The specific steps are as follows:
[0015] Solid-liquid separation is carried out at room temperature, and the obtained solid precipitate is washed multiple times with ultrapure water. The washed solid precipitate is placed in a 90°C forced air drying oven and dried for 24 hours, thereby completing the preparation of the smithsonite-cerussite series solid solution and realizing the long-term storage of lead-zinc waste slag in the environment.
[0016] Leaching test: Weigh 10g of the synthetic smithsonite-cerussite series solid solution samples and place them in 3 groups of 5L polyethylene terephthalate (PET) bottles. Add 5L of nitrogen-degassed ultrapure water, air-saturated ultrapure water, and carbon dioxide-saturated ultrapure water to each group of bottles. Seal the PET bottles, shake them gently, and dissolve them at room temperature (air conditioning 25°C). During the dissolution process, take a certain volume of supernatant sample at 1h, 3h, 6h, 12h, 1d, 2d, 3d, 5d, 10d, 15d, 20d, 30d, 40d, 50d, 60d, 70d, 80d, 90d, 120d, and 150d (h means hours, d means days) to determine Pb 2+ 、Zn 2+ The concentration of lead and zinc is obtained by leaching. After 150 days of leaching, the leaching concentration of the smithsonite-cerussite series solid solution under air and nitrogen degassed ultrapure water conditions is low, while the leaching concentration under carbon dioxide saturated ultrapure water conditions is higher than the former two. It can be seen that when the smithsonite-cerussite series solid solution is piled up in the environment, it cannot be in contact with acidic substances or piled together to avoid lead and zinc pollution accidents.
[0017] The present invention utilizes lead and zinc cations to coprecipitate with carbonate anions to generate carbonate series solid solutions containing lead and zinc. The smithsonite-cerussite series solid solutions synthesized by the method can effectively remove heavy metal elements lead and zinc in aqueous solution, and the leaching concentration in water environment under neutral and alkaline conditions is very high. After a long period of dissolution, the leaching concentration of lead and zinc ions slowly decreases, and reaches equilibrium after dropping to a lower level. Therefore, the carbonate solidification zinc and lead obtained by the present invention to prepare the smithsonite-cerussite series solid solutions can effectively remove lead and zinc in wastewater, and realize the long-term stacking of lead-zinc waste residues in the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The XRD diagrams of the smithsonite-cerussite series solid solutions prepared in Examples 1 to 5 of the present invention, wherein the smithsonite standard card is PDF#00-008-0449, and the cerussite standard card is PDF#00-047-1734.
[0019] Figure 2 This is a scanning electron microscope image (SEM) of the smithsonite solid solution prepared in Example 1 of the present invention.
[0020] Figure 3 This is a scanning electron microscope image (SEM) of the cerussite solid solution obtained in Example 5 of the present invention. DETAILED DESCRIPTION
[0021] Example 1
[0022] At room temperature, 25 mL of 0.5 mol / L zinc nitrate solution was measured in a 600 mL beaker, and the beaker was placed on an intelligent magnetic stirrer, and the stirrer speed was set to 500 r / min. At the same time, carbon dioxide gas was introduced into the solution; after about 15 minutes, 500 mL of 0.5 mol / L NH4HCO3 solution was added dropwise to the beaker at a certain time interval; after the reaction was completed, the beaker was sealed with plastic wrap and aged for 2 days; the pH value of the supernatant was measured with a desktop pH meter and filtered. During the filtration process, the beaker was washed with ultrapure water 3 times and anhydrous ethanol once. The obtained solid sample was dried in a 90℃ forced air drying oven for 24 hours to obtain a smithsonite solid solution. The smithsonite obtained in this process removed more than 90% of the zinc in the aqueous solution.
[0023] Leaching test:
[0024] Degassed ultrapure water, dissolution for 150 days at 25°C, zinc leaching concentration 0.0982 mmol / L;
[0025] Air-saturated ultrapure water, dissolved for 150 days at 25°C, zinc leaching concentration 0.1182 mmol / L;
[0026] Carbon dioxide saturated ultrapure water, dissolved at 25°C for 150 days, zinc leaching concentration is 0.1984 mmol / L.
[0027] Example 2
[0028] At room temperature, 17.5 mL of 0.5 mol / L zinc nitrate solution and 7.5 mL of 0.5 mol / L lead nitrate solution were measured in a 600 mL beaker, and the beaker was placed on an intelligent magnetic stirrer, and the stirrer speed was set to 500 r / min. At the same time, carbon dioxide gas was introduced into the solution; after about 15 minutes, 500 mL of 0.5 mol / L NH4HCO3 solution was added dropwise to the beaker at a certain time interval; after the reaction was completed, it was sealed with plastic wrap and aged for 2 days; the pH value of the supernatant was measured with a desktop pH meter and filtered. During the filtration process, the beaker was washed with ultrapure water 3 times and anhydrous ethanol once. The obtained solid sample was dried in a 90℃ forced air drying oven for 24 hours to obtain a smithsonite-cerussite solid solution with a lead nitrate / (zinc nitrate + lead nitrate) molar ratio of 0.30.
[0029] Leaching test:
[0030] Degassed ultrapure water, dissolving for 150 days at 25°C, zinc leaching concentration is 0.1861 mmol / L, lead leaching concentration is 0.0004 mmol / L;
[0031] Air-saturated ultrapure water, dissolved at 25°C for 150 days, zinc leaching concentration is 0.1914 mmol / L, lead leaching concentration is 0.0004 mmol / L;
[0032] Carbon dioxide saturated ultrapure water, dissolved at 25°C for 150 days, zinc leaching concentration is 0.3530 mmol / L, lead leaching concentration is 0.0008 mmol / L.
[0033] Example 3
[0034] At room temperature, 12.5 mL of 0.5 mol / L zinc nitrate solution and 12.5 mL of 0.5 mol / L lead nitrate solution were measured in a 600 mL beaker, and the beaker was placed on an intelligent magnetic stirrer, and the stirrer speed was set to 500 r / min. At the same time, carbon dioxide gas was introduced into the solution; after about 15 minutes, 500 mL of 0.5 mol / L NH4HCO3 solution was added dropwise to the beaker at a certain time interval; after the reaction was completed, the beaker was sealed with plastic wrap and aged for 2 days; the pH value of the supernatant was measured with a desktop pH meter and filtered. During the filtration process, the beaker was washed with ultrapure water 3 times and anhydrous ethanol once. The obtained solid sample was dried in a 90℃ forced air drying oven for 24 hours to obtain a smithsonite-cerussite solid solution with a molar ratio of lead nitrate / (zinc nitrate + lead nitrate) of 0.50.
[0035] Leaching test:
[0036] Nitrogen degassed ultrapure water, dissolving for 150 days at 25°C, zinc leaching concentration is 0.1773 mmol / L, lead leaching concentration is 0.0004 mmol / L;
[0037] Air-saturated ultrapure water, dissolved at 25°C for 150 days, zinc leaching concentration is 0.1864 mmol / L, lead leaching concentration is 0.0004 mmol / L;
[0038] Carbon dioxide saturated ultrapure water, dissolved at 25°C for 150 days, zinc leaching concentration is 0.3981 mmol / L, lead leaching concentration is 0.0008 mmol / L.
[0039] Example 4
[0040] At room temperature, 5.0 mL of 0.5 mol / L zinc nitrate solution and 20.0 mL of 0.5 mol / L lead nitrate solution were measured in a 600 mL beaker, and the beaker was placed on an intelligent magnetic stirrer, and the stirrer speed was set to 500 r / min. At the same time, carbon dioxide gas was introduced into the solution; after about 15 minutes, 500 mL of 0.5 mol / L NH4HCO3 solution was added dropwise to the beaker at a certain time interval; after the reaction was completed, it was sealed with plastic wrap and aged for 2 days; the pH value of the supernatant was measured with a desktop pH meter and filtered. During the filtration process, the beaker was washed with ultrapure water 3 times and anhydrous ethanol once. The obtained solid sample was dried in a 90℃ forced air drying oven for 24 hours to obtain a smithsonite-cerussite solid solution with a molar ratio of lead nitrate / (zinc nitrate + lead nitrate) of 0.80.
[0041] Leaching test:
[0042] Nitrogen degassed ultrapure water, dissolving for 150 days at 25°C, zinc leaching concentration is 0.1732 mmol / L, lead leaching concentration is 0.0004 mmol / L;
[0043] Air-saturated ultrapure water, dissolved at 25°C for 150 days, zinc leaching concentration is 0.1962 mmol / L, lead leaching concentration is 0.0004 mmol / L;
[0044] Carbon dioxide saturated ultrapure water, dissolved at 25°C for 150 days, zinc leaching concentration is 0.5605 mmol / L, lead leaching concentration is 0.0009 mmol / L.
[0045] Example 5
[0046] At room temperature, 25 mL of 0.5 mol / L lead nitrate solution was measured in a 600 mL beaker, and the beaker was placed on an intelligent magnetic stirrer, and the stirrer speed was set to 500 r / min. At the same time, carbon dioxide gas was introduced into the solution; after about 15 minutes, 500 mL of 0.5 mol / L NH4HCO3 solution was added dropwise to the beaker at a certain time interval; after the reaction was completed, it was sealed with plastic wrap and aged for 2 days; the pH value of the supernatant was measured with a desktop pH meter and filtered. During the filtration process, the beaker was washed with ultrapure water 3 times and anhydrous ethanol once. The obtained solid sample was dried in a 90℃ forced air drying oven for 24 hours to obtain a cerussite solid solution. The removal rate of lead in aqueous solution obtained by the cerussite in this process was close to 100%.
[0047] Leaching test:
[0048] Nitrogen degassed ultrapure water, dissolved at 25°C for 150 days, lead leaching concentration 0.0132 mmol / L;
[0049] Air-saturated ultrapure water, dissolved for 150 days at 25°C, lead leaching concentration 0.0110 mmol / L;
[0050] Carbon dioxide saturated ultrapure water, dissolved at 25°C for 150 days, the lead leaching concentration was 0.0409 mmol / L.
Claims
1. A method for preparing a smithsonite-cerussite series solid solution by solidifying zinc and lead with carbonates, characterized in that: The specific steps are: (1) Prepare fresh ultrapure water, weigh an appropriate amount of ammonium bicarbonate solid, and prepare a 0.5 mol / L ammonium bicarbonate solution for later use; weigh an appropriate amount of zinc nitrate solid, and prepare a 0.5 mol / L zinc nitrate solution for later use; weigh an appropriate amount of lead nitrate solid, and prepare a 0.5 mol / L lead nitrate solution for later use; (2) In a clean beaker, prepare 25 mL of a 0.5 mol / L mixed solution of Zn(NO3)2 and Pb(NO3)2 with Pb / (Zn+Pb) molar ratios of 0.000, 0.002, 0.004, 0.006, 0.008, 0.010, 0.015, 0.020, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.82, 0.84, 0.86, 0.88, 0.90 and 1.00, respectively; (3) Take 22 clean 600 mL beakers and add the mixed solution according to the molar ratio in step (2); (4) At room temperature, in a clean beaker, introduce carbon dioxide gas at a flow rate of 6-9 L / min into the mixed solution and set the stirring speed to 500 r / min; (5) Add 500 mL of 0.5 mol / L NH4HCO3 solution to the mixed solution of Zn(NO3)2 and Pb(NO3)2; (6) After aging for 2 days, the pH value of the supernatant is measured, and solid-liquid separation is performed at room temperature. The obtained solid phase precipitate is washed with ultrapure water for multiple times, and the washed solid phase precipitate is placed in a 90°C forced air drying oven and dried for 24 hours. This completes the preparation of the smithsonite-cerussite series solid solution, and realizes the long-term storage of lead-zinc waste slag in the environment.
2. An application of the carbonate prepared by the method of claim 1 to solidify zinc and lead to prepare a series of smithsonite-cerussite solid solutions, characterized in that It can be used to remove lead and zinc from wastewater and to store lead-zinc waste residues in the environment for a long time, as follows: Leaching tests were carried out on the smithsonite-cerussite series solid solutions in nitrogen degassed ultrapure water, air saturated ultrapure water, and carbon dioxide saturated ultrapure water. The results were as follows: under degassed ultrapure water conditions, the zinc leaching concentration was 0.1861 mmol / L and the lead leaching concentration was 0.0004 mmol / L after 150 days of dissolution; under air saturated ultrapure water conditions, the zinc leaching concentration was 0.1914 mmol / L and the lead leaching concentration was 0.0004 mmol / L after 150 days of dissolution; under carbon dioxide saturated ultrapure water conditions, the zinc leaching concentration was 0.3530 mmol / L and the lead leaching concentration was 0.0008 mmol / L after 150 days of dissolution.